2005
DOI: 10.1152/ajpregu.00360.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic maternal feed restriction impairs growth but increases adiposity of the fetal guinea pig

Abstract: Small size at birth has been associated with an increased risk of central obesity and reduced lean body mass in adult life. This study investigated the time of onset of prenatally induced obesity, which occurs after maternal feed restriction, in the guinea pig, a species that, like the human, develops substantial adipose tissue stores before birth. We examined the effect of maternal feed restriction [70% ad libitum intake from 4 wk before to midpregnancy, then 90% until day 60 gestation (term ∼69 days)] on fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 50 publications
6
58
0
1
Order By: Relevance
“…In guinea pigs, maternal undernutrition increases the relative adiposity of the fetus and appears to preserve WAT at the expense of BAT in the interscapular depots (24). In sheep, maternal nutrient restriction in late gestation results in a 2.5-fold decrease in the abundance of UCP1 mRNA in near-term fetal adipose tissue, but there is no effect on protein abundance at this stage (6).…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pigs, maternal undernutrition increases the relative adiposity of the fetus and appears to preserve WAT at the expense of BAT in the interscapular depots (24). In sheep, maternal nutrient restriction in late gestation results in a 2.5-fold decrease in the abundance of UCP1 mRNA in near-term fetal adipose tissue, but there is no effect on protein abundance at this stage (6).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it has been shown that IUGR might be responsible for somatic growth alterations leading to shorter (body length) and lighter (body weight) rat offspring (21,25,53,55). Thus, in addition to skeletal growth modifications (16,21), we cannot rule out the possibility that a different lean-to-fat mass ratio due to a deficit in muscle mass and/or different body fat pad distribution occurs in adult FR30 rats (25). To address this question, further experiments, such as absorptiometric studies, are needed to measure the total body composition of FR30 adult rats.…”
Section: Discussionmentioning
confidence: 99%
“…Foetal growth potential is controlled at many levels; however one very critical factor is that of the in utero maternal environment. Maternal feed restriction, through experimental approaches or food shortage, like that of the Dutch famine during World War II, has been correlated with low birth weight and subsequent changes in endocrine, metabolic and reproductive parameters in these offspring later in life, as well as predisposition to certain cancers [17][18][19][20][21][22][23][24][25][26]. It is hypothesised that these changes in endocrine and metabolic parameters are in essence programming the offspring for the development of endocrine associated adult diseases.…”
Section: Early Origins Of Adult Disease and Foetal Programmingmentioning
confidence: 99%